The soil in which we root: redeﬁning a Ugandan "Museum" in a 21st Century Post-Colonial world - Rubombora, Valerie Mary Nyamwoni (My University, 2017)
Uganda is one of the most ethnically diverse countries on the planet. Under half a century of colonialist rule, the country was subjected to a loss of identity through a painful process of demoralizing propaganda and subordination that sought to create of it a consistently dependent market. Over 50 years after independence, the country is still suffering the repercussions of our recoded identity. The colonial code ensures a people that are constantly subjugated to a foreign, imperialist power, and only through recoding the colonial will we be able to take back the power of self-definition that has defined our post-colonial, neo-colonial state. The soil in which I root is an investigation into the origins and influence of the colonial in the development of national identity in Uganda within the context of Sub-Saharan African states. This research will be investigating appropriate influences, in terms of contextual relation and monumentality, which have been employed in the development of identity: looking particularly into two approaches to national identity generation – the personality cult and the anti-monument. This is conducted in order to determine an appropriate response to a Ugandan “museum” of political history – designed to contradict the existing, colonial, introspective building – within the context of Kampala city. With 70% of the population under the age 24 and the highest ethnic diversity in the world there is an urgent need to recognize Uganda’s identity as a post-independent society, in order for the development of a national self-efficacy and self-determination determination.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--Uganda; Public spaces--Uganda; Museums--Uganda